REBELS AND HERETICS: THE IQUICHANOS IN INDEPENDENCE AND THE RISING PERUVIAN REPUBLIC (Tzintzun, Revista de Estudios Históricos, 2023)
This article studies the link of the Iquichanos with the viceregal administration,their participation in the process of the Independence of Peru and the reasonsfor the prolonging of the Iquichan rebellion. From the analysis of unpublishedsources, we consider that the Iquichanos identified with the Spanish crown inexchange for having certain privileges. During the Independence they defeatedthe Cuzco rebellion of 1814 and harassed Sucre’s forces. Towards the first yearsof the republican government, they led a rebellion not only for economic reasons,but also because they were affected by the jurisdictional reorganizations and theprohibition of their cultural expressions.
Keywords: rebellion; Iquicha; Ayacucho; Independence; republic; Peru